2002
DOI: 10.1080/003655902320131901
|View full text |Cite
|
Sign up to set email alerts
|

Suspicious Urine Cytology (Class III) in Patients with Bladder Cancer: Should it be Considered as Negative or Positive?

Abstract: The poor sensitivity of voided urine cytology improved significantly when suspicious samples were determined as positive while the specificity remained high, a clear advantage compared with most of the new tumour marker tests. In addition, nearly half of the follow-up patients with suspicious class III cytology had recurrence implying that this patient category is at substantial risk for co-existing malignancy. Therefore, it is recommended that suspicious class III cytology together with class IV and V specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 5 publications
1
34
0
Order By: Relevance
“…A total of 47 studies, reported in 56 papers, were diagnostic cross-sectional studies, 45,80,97,98,100-103,105, 109-129,131-133,135,136,139-141, 145,146,148-153,165-174 of which 11 45,101,109,110,112,116,118,126,127,165,174 reported consecutive recruitment. Nine studies 107,108,155,[157][158][159][162][163][164] were case-control studies and 11 studies 103,108,111,116,126,127,135,149,165,170,174 were multicentre ( Table 19).…”
Section: Cytology Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 47 studies, reported in 56 papers, were diagnostic cross-sectional studies, 45,80,97,98,100-103,105, 109-129,131-133,135,136,139-141, 145,146,148-153,165-174 of which 11 45,101,109,110,112,116,118,126,127,165,174 reported consecutive recruitment. Nine studies 107,108,155,[157][158][159][162][163][164] were case-control studies and 11 studies 103,108,111,116,126,127,135,149,165,170,174 were multicentre ( Table 19).…”
Section: Cytology Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Nine studies 107,108,155,[157][158][159][162][163][164] were case-control studies and 11 studies 103,108,111,116,126,127,135,149,165,170,174 were multicentre ( Table 19). …”
Section: Cytology Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we found that among the samples categorized as atypical, indeterminate, and suspicious of malignancy, the numbers of concommitant cancerous lesions were 105 (23.6%), 147 (40.1%), and 139 (49.8%), respectively. Raitanen et al (Raitanen et al, 2002) addressed the question of whether, in a population of patients diagnosed with bladder cancer, class III urine cytology should be considered as a negative or positive indication for the presence of cancerous lesions; these investigators recommended that class III cytology should be considered as positive. Several reports have shown that assuming class III reports to be positive instead of negative improves sensitivity while maintaining acceptable specificity.…”
Section: Discussionmentioning
confidence: 99%